Chinese immigrants’ parental experiences in Norway - Zhu, Hong (2015)
Existing empirical studies of parents in China found that this population presents features of authoritarian parenting style: greater parental demands and control together with lower parental responsiveness. However, when the investigation conducted on Chinese immigrants, parental practice is characterized as more authoritative style, combining high levels of controlling and responsiveness. Paradoxical findings between Chinese parents and Chinese immigrant parents raised the research interest in investigating the influence of acculturation on the change of parental behavior among this particular immigrants group. In addition, although some researchers contributed their writing on Chinese immigrant parents’ acculturation in North America (USA and Canada), similar detailed studies remained rare in Scandinavian countries, Norway particularly, where the Chinese immigrants are seen as one of fastest growing ethical population. In response to existing literature gap, the current research aimed to achieve a fundamental understanding of Chinese immigrants’ parental experience in Norway and its relation with individual acculturation. Through the narrative inquiry of five Chinese immigrant parents from three individual families, this dissertation uncovered multiple realities associated with parenting experiences built via Chinese immigrant parents in their personal, contextual, and time variables. Guiding this inquiry was the Bioecological and Acculturation models, which offered the overarching theoretical frameworks to help addressing various determinants which shape the respondents’ parental beliefs and behaviors. With a focus on parents’ critical events related to childrearing in Norway, data was collected through the open-ended and in-depth interviews and was presented in two approaches: case-focused narrative analysis and cross-case content analysis. The findings showed respondents’ parental behavior is one of the outcomes of personal interaction with their ecological system. Participants’ parental practice in Norway was gradually shaped and changed due to these people’s relation to multiple factors at three main levels resided in ecological system: namely personal features (e.g. individuals’ personal history, social-economic and employment status, the perception of mother role, etc); contextual factors (e.g. spouse, friends, extended family members, Norwegian school, cultural values from China and Norway); and acculturation. Further, Chinese immigrant parents found in this dissertation facing significant parental stresses stem from contextual challenges and problems including lack of social support, downward social mobility, language barriers, downgraded social and economic status, discrimination, and expectation of children’s academic achievement. The role of individual acculturation degree was essential in selected Chinese parents’ parental behavior. Greater parental acculturation tended to be more associated with healthier family relationship and positive parenting. Being acculturated allows parents to have multiple insights to examine the criterion constructed the image of good parenting within specific contexts. Social supports in this research were identified as the mediator of parental stress and the accelerator of parental acculturation. The positive relationship with, or supports from the spouse, extended family, friends, and other social networks, were essential in easing parental stress in respect of immigration, acculturation, and parenting. The new empirical findings in this dissertation could help the social work and social policy field to build a more detailed image towards Chinese immigrants in Norway and further better identify the demand for support and services in parenting and child development for this specific ethnic population. Multiple improvements could be implemented to help remitting Chinese parental pressures, supporting them in transition of cultures, and strengthening their social support networks. Since Chinese immigrant parents’ social network found sitting central position in balancing parental stress and acculturation level for promoting a better parenting practice, the author further suggested to enhance Chinese immigration parents’ social network in reference of social capital theory. As the significant dimension of social capital, the social network could be expanded through bonding and bridging strategies. Practically, bonding include strategies with the aim of improving Chinese immigrants pre-existing networks with other Chinese in Norway, such as the establishment of the Chinese organization at local and national level. Bridging, however, indicates approaches that encourage the targeted immigration population to get beyond their preoccupation with common bonds and engage in cross-cultural relation building. The example of bridging capital could be the operation of an interest-oriented community/club, such as the parents’ clubs, which allow Chinese immigrant parents to extend their reliance on other ethnic or native parents in Norway.